Evaluation of Microbiological Quality of Indigenous Dahi from Eastern Nepal - Bhattarai, Rewati Raman; Das, Suman Kumar Lal (2016)
The present study was undertaken to evaluate the microbiological quality of indigenous dahi from eastern Nepal. Atotal of 39 indigenous dahi samples were collected from sixteen districts of eastern Nepal and analyzed. Results revealed the mean yeasts and mould count to be 20.5×104±7503, coliform count 65±42, S. aureus 197±65 and total viable bacterial count 227×106±17250 cfu/g. Total viable bacteria and yeasts and moulds were present in all samples examined. Coliforms were present in 90 % and S. aureus were present in 63% of samples examined whereas salmonella species were not detected in any of the samples under study.